THE IMPACT OF SOCIAL MEDIA MARKETING AND CUSTOMER EXPERIENCE ON CUSTOMER BEHAVIOUR WITH RELATIONSHIP QUALITY AS AN INTERVENING VARIABLE: CASE STUDY ON ERIGO CLOTHING BRAND - Zappelin, Alvencius; Kembau, Agung Stefanus; Tarigan , Arithta; Mandey, Nancy Henrietta Jessamine (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
Following the development of technology, people are more inclined to buy fashion products online instead of going to physical stores. Erigo also changed its sales channel to entirely online and experienced a drastic increase in sales. This research was conducted to find out whether the sales strategy carried out by Erigo is effective for online sales. This study used quantitative methods and obtained data from questionnaires distributed online which resulted in 105 respondents who met the criteria. The data was analyzed using SmartPLS 3.0 software with Partial Least Square technique. The sample was determined using purposive sampling and determined by the Cochran formula. The results of the study indicate that all hypotheses are accepted. The research shows that Social Media Marketing and Customer Experience have a significant influence on Relationship Quality and Relationship Quality significantly affects Purchase Intention, Loyalty Intention and Participation Intention. Keywords:Social Media Marketing, Customer Experience, Relationship Quality, Purchase Intention, Loyalty Intention, Participation Intenton, Erigo